2013
DOI: 10.1111/cdev.12157
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity Complexity, Cross‐Ethnic Friendships, and Intergroup Attitudes in Urban Middle Schools

Abstract: The current study investigated contextual antecedents (i.e., cross-ethnic peers and friends) and correlates (i.e., intergroup attitudes) of social identity complexity in seventh grade. Social identity complexity refers to the perceived overlap among social groups with which youth identify. Identifying mostly with out-of-school sports, religious affiliations, and peer crowds, the ethnically diverse sample (N = 622; Mage in seventh grade = 12.56) showed moderately high complexity. Social identity complexity medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 66 publications
3
49
0
3
Order By: Relevance
“…Relying on a relatively novel construct, social identity complexity, we demonstrated that such complexity also helps account for the association between earlier exposure to cross‐ethnic peers in extracurricular activities and subsequent intergroup attitudes. Extending prior research on school‐based availability of cross‐ethnic peers (Knifsend & Juvonen, ), we showed that exposure to other ethnic groups in extracurricular activities in sixth grade is related to more complex and inclusive social identities in seventh grade. Consistent with research on adults living in ethnically diverse neighborhoods, greater social identity complexity, in turn, was associated with more positive ethnic intergroup attitudes (i.e., lower social distance) at the same time point (Schmid et al., ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Relying on a relatively novel construct, social identity complexity, we demonstrated that such complexity also helps account for the association between earlier exposure to cross‐ethnic peers in extracurricular activities and subsequent intergroup attitudes. Extending prior research on school‐based availability of cross‐ethnic peers (Knifsend & Juvonen, ), we showed that exposure to other ethnic groups in extracurricular activities in sixth grade is related to more complex and inclusive social identities in seventh grade. Consistent with research on adults living in ethnically diverse neighborhoods, greater social identity complexity, in turn, was associated with more positive ethnic intergroup attitudes (i.e., lower social distance) at the same time point (Schmid et al., ).…”
Section: Discussionsupporting
confidence: 78%
“…The second mediator tested, social identity complexity, was assessed using a measure based on an adult version (Brewer & Pierce, ; Roccas & Brewer, ), developed by Knifsend and Juvonen (, ). As mentioned earlier, social identity complexity was first measured in the seventh grade to afford youth the time to develop meaningful social identities in a new school context.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ethnic groups included Asian, African American, Latino, and White youth. Following methods outlined by Knifsend and Juvonen (), we computed for each participant an aggregated measure of social distance from all three ethnic out‐groups. Social distance was calculated by subtracting the average of the 12 items for three ethnic out‐groups from the average of four items for members of one's own ethnic in‐group (α = .93).…”
Section: Methodsmentioning
confidence: 99%
“…We selected sixth graders because friendships take on added significance in early adolescence (Brechwald & Prinstein, ) and increased social‐cognitive maturity along with more social exposure during the transition to middle school make ethnicity more salient to young adolescents (Umaña‐Taylor et al., ). In addition, social identities, including those about race, that highlight boundaries between in‐group and out‐groups become increasingly important during adolescence (Knifsend & Juvonen, ; Sani & Bennett, ). Using peer nominations, we studied Asian students’ friendships with grade‐mates who were White, Black, and Latino.…”
Section: Determinants Of Cross‐ethnic Friendshipsmentioning
confidence: 99%